The Classroom Infrastructure and the Early Learner: Reducing Aggression During Transition Times - Guardino, Caroline; Fullerton, Elizabeth Kirby (Journal of the American Academy of Special Education Professionals, 2012)
High levels of aggressive behaviors were observed during the transition times in two selfcontained special education classrooms: a kindergarten and pre-kindergarten. The present case studies examine how modifying the classroom infrastructure impacts students’ aggressive behavior. Teachers were assisted on the usage of select modifications (visual cues and carrels). Data were collected during pre-experimental, baseline, intervention 1, and intervention 2. Results indicate that modifying the classroom environment decreased aggressive behaviors during transition times by as much as 12% from the beginning of the study. The change in aggressive behavior was moderate and teachers perceived the intervention as having a positive impact on students’ learning and their ability to teach. Implications for practitioners are discussed.